Breakthrough infections with the omicron and delta variants of SARS-CoV-2 result in similar re-activation of vaccine-induced immunity - Søraas, Arne; Grødeland, Gunnveig; Granerud, Beathe Kiland; Ueland, Thor; Lind, Andreas; Fevang, Børre; Murphy, Sarah L.; Huse, Camilla; Nygaard, Anders Benteson; Steffensen, Anne Katrine; al-Baldawi, Huda; Holberg-Petersen, Mona; et al. (Frontiers in Immunology, 2022)
Background: Results showing that sera from double vaccinated individuals have minimal neutralizing activity against Omicron have been interpreted as indicating the need for a third vaccine dose for protection. However, there is little information about early immune responses to Omicron infection in double vaccinated individuals. Methods: We measured inflammatory mediators, antibodies to the SARS-CoV-2 spike and nucleocapsid proteins, and spike peptide-induced release of interferon gamma in whole blood in 52 double-vaccinated individuals infected with Omicron, in 18 infected with Delta, and in 14 healthy controls. The median time points for the first and second samples were 7 and 14 days after symptom onset, respectively. Findings: Infection with Omicron or Delta led to a rapid and similar increase in antibodies to the receptor-binding domain (RBD) of Omicron protein and spike peptide-induced interferon gamma in whole blood. Both the Omicron- and the Delta-infected patients had a mild and transient increase in inflammatory parameters. Interpretation: The results suggest that two vaccine doses are sufficient to mount a rapid and potent immune response upon infection in healthy individuals with the Omicron variant. Funding: The study was funded by the Oslo University Hospital, and by grants from The Coalition for Epidemic Preparedness Innovations, Research Council of Norway (no 312780, 324272), South-Eastern Norway Regional Health Authority (no 2019067, 2021071, 10357, 2021047, 33612, 2021087, 2017092), EU Horizon 2020 grant no 848099, a philantropic donation from Vivaldi Invest A/S owned by Jon Stephenson von Tetzchner, and The European Virus Archive Global.